The girl before : a novel - Delaney, J P (New York : Ballantine Books, 2017)
"In the tradition of The Girl on the Train, The Silent Wife, and Gone Girl comes an enthralling psychological thriller that spins one woman's seemingly good fortune, and another woman's mysterious fate, through a kaleidoscope of duplicity, death, and deception. Please make a list of every possession you consider essential to your life. The request seems odd, even intrusive--and for the two women who answer, the consequences are devastating. EMMA Reeling from a traumatic break-in, Emma wants a new place to live. But none of the apartments she sees are affordable or feel safe. Until One Folgate Street. The house is an architectural masterpiece: a minimalist design of pale stone, plate glass, and soaring ceilings. But there are rules. The enigmatic architect who designed the house retains full control: no books, no throw pillows, no photos or clutter or personal effects of any kind. The space is intended to transform its occupant--and it does. JANE After a personal tragedy, Jane needs a fresh start. When she finds One Folgate Street she is instantly drawn to the space--and to its aloof but seductive creator. Moving in, Jane soon learns about the untimely death of the home's previous tenant, a woman similar to Jane in age and appearance. As Jane tries to untangle truth from lies, she unwittingly follows the same patterns, makes the same choices, crosses paths with the same people, and experiences the same terror, as the girl before. Advance praise for The Girl Before "Dazzling, startling, and above all cunning--a pitch-perfect novel of psychological suspense."--Lee Child "Riveting! One of the most compelling page-turners I've read in years. Twisty, turny, and with an ending not to be missed!"--Lisa Gardner"--
"A psychological thriller that spins one woman's seemingly good fortune, and another woman's mysterious fate, through a kaleidoscope of duplicity, death, and deception"--
Keywords: Architects -- Fiction; Single women -- Fiction; Dwellings -- Fiction; Control (Psychology) -- Fiction; FICTION / Suspense; FICTION / Literary; Architects; Control (Psychology); Dwellings; Single women; Architects -- Fiction; Single women -- Fiction; Control (Psychology) -- Fiction; Dwellings -- Fiction; FICTION / Literary; FICTION / Thrillers; FICTION / Suspense; Psychological fiction; FICTION / Thrillers; Suspense fiction; Thrillers (Fiction); Fiction; Psychological fiction; Suspense fiction; Suspense fiction; Psychological fiction